HBR's 10 Must Reads on Leadership, Vol. 2 - Review, Harvard (Ascent Audio, 2020)
Stay on top of your leadership game. Leadership isn't something you're born with or gifted as a reward for an abundance of charisma; true leadership stems from core skills that can be learned. Get more of the leadership ideas you want, from the authors you trust, with HBR's 10 Must Reads on Leadership (Vol. 2). We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you maximize your own and your organization's performance. With insights from leading experts including Michael D. Watkins, Herminia Ibarra, and Michael E. Porter, this book will inspire you to: identify areas for personal growth; build trust with and among your employees; develop a more dynamic and sophisticated communication style; try out different leadership styles and behaviors to find the right approach for you-and your organization; transform yourself from a problem solver to an agenda setter; harness the power of connections; and become an adaptive and strategic leader.
Online resource; Title from title page (viewed March 24, 2020)
Keywords: Business; Affaires; Audiobooks